The Labor Force Decision of Married Female Teachers: A Reply - Gramm, Wendy Lee (The Review of Economics and Statistics, 1976)
children indicate that women with older children tend to be in the full-time group. The negative coefficients for the ages of the second and fourth children themselves imply that individuals with high values for these variables are least likely to be classified as full-time workers. The interactions between the children or the non-linearity of the relation between ages and the labor supply behavior of the wife probably account for the alternating signs.9